A novel real-time shapeable soft rubber bolus for clinical use in electron radiotherapy. (14th September 2021) - Wakabayashi, Kazuki; Monzen, Hajime; Tamura, Mikoto; Takei, Yoshiki; Okuhata, Katsuya; Anami, Shimpei; Doi, Hiroshi; Nishimura, Yasumasa
Abstract: We have developed soft rubber (SR) bolus that can be shaped in real-time by heating flexibly and repeatedly. This study investigated whether the SR bolus could be used as an ideal bolus, such as not changing of the beam characteristics and homogeneity through the bolus and high plasticity to adhere a patient in addition to real-time shapeable and reusability, in electron radiotherapy. Percentage depth doses (PDDs) and lateral dose profiles (LDPs) were obtained for 4, 6, and 9 MeV electron beams and were compared between the SR and conventional gel boluses. For the LDP at depth of 90% dose, the penumbra as lateral distance between the 80% and 20% isodose lines ( P 80 − 20 ) and the width of 90% dose level ( r 90 ) were compared. To evaluate adhesion, the air gap volume between the boluses and nose of a head phantom was evaluated on CT image. The dose profiles along the center axis for the 6 MeV electron beam with SR, gel, and virtual boluses (thickness = 5 mm) on the head phantom were also calculated for the irradiation of 200 monitor unit with a treatment planning system and the depth of the maximum dose ( d max ) and maximum dose ( D max ) were compared. The PDDs, P 80 − 20, and r 90 between the SR and gel boluses corresponded well (within 2%, 0.4 mm, and 0.7 mm, respectively). The air gap volumes of the SR and gel boluses were 3.14 and 50.35 cm 3, respectively. The d max with SR, gel and virtual boluses were 8.0, 6.0, and 7.0 mm (no bolus: 12.0 mm), and the D max values were 186.4, 170.6, and 186.8 cGy, respectively. The SR bolus had the equivalent electron beam characteristics and homogeneity to the gel bolus and achieved excellent adhesion to a body surface, which can be used in electron radiotherapy as an ideal bolus.